Przebieg kształcenia w orkiestrach dętych = Training course in brass orchestras - Zycha-Gurdek, Adriana (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The following article has been characterized by the course of training in brass orchestras. Three stages of education were identified and the results were shown in a graphical chart. The article provides guidance for the work of teachers-instructors and hats with instrumentalists at different stages of education.
Keywords: edukacja; kształcenie; proces edukacji; kształcenie muzyczne; edukacja muzyczna; etapy kształcenia; komunikaty; cele kształcenia; metody nauczania; środki kształcenia; proces kształcenia; education; educational process; music education; learning stages; communication; learning objectives; teaching methods; educational measures; learning process